A mediating effect of trust on the relationship between consumer consumption factor on the Iranian online shopping behavior: a diffusion of innovation approach - Sara, Temouri (Indonesia Research and Study Center, 2025)
The rapid expansion of e-commerce in Iran has significantly transformed consumer shopping behavior. This study examines the mediating effect of trust on the relationship between consumer consumption factors and online shopping behavior in Iran, applying the Diffusion of Innovation (DOI) framework. The DOI theory explains how consumers adopt new technologies and shopping platforms, influenced by factors such as perceived usefulness, ease of use, risk perception, and social influence. However, trust remains a crucial determinant in online transactions, acting as a bridge between consumer preferences and actual purchasing behavior. Using a quantitative approach, this study analyzes survey data from Iranian online shoppers to assess how trust influences their adoption of e-commerce platforms. Findings reveal that while consumer consumption factors significantly impact online shopping behavior, trust plays a pivotal mediating role, enhancing the adoption rate. This research contributes to both theoretical and practical discussions on digital commerce, providing insights for e-commerce businesses and policymakers aiming to foster trust and boost online retail adoption in Iran.